Impact of of Mindfulness-Based Group Interventions on Attention Regulation and Emotional Maturity in Adolescents - Kalogeropoulos, Dimitra; Papadopoulos, Eleni (KMAN Counseling & Psychology Nexus, 2025)
This study aimed to evaluate the effectiveness of a mindfulness-based group intervention on attention regulation and emotional maturity in adolescents. A randomized controlled trial was conducted with 30 adolescent participants from secondary schools in Athens, Greece. Participants were randomly assigned to an experimental group (n = 15) that received a ten-session mindfulness-based group intervention, or a control group (n = 15) that received no intervention. The intervention was delivered in weekly 60-minute sessions over a period of ten weeks. Data were collected at three stages: pre-test, post-test, and five-month follow-up. Attention regulation was assessed using the Attention Control Scale (Derryberry & Reed, 2002), and emotional maturity was measured with the Emotional Maturity Scale (Singh & Bhargava, 1991). Data analysis was performed using repeated measures ANOVA with Bonferroni post-hoc tests in SPSS-27. Descriptive statistics indicated improvements in attention regulation (Pre-test: M = 52.67, SD = 4.21; Post-test: M = 58.80, SD = 3.72) and emotional maturity (Pre-test: M = 152.40, SD = 6.88; Post-test: M = 138.53, SD = 7.41) in the experimental group, with gains maintained at five-month follow-up. Repeated measures ANOVA showed significant time × group interaction effects for both attention regulation (F(2, 54) = 11.83, p < .001, η² = .41) and emotional maturity (F(2, 54) = 16.53, p < .001, η² = .48). Bonferroni post-hoc tests confirmed significant improvements from pre-test to post-test and pre-test to follow-up in the experimental group, with no significant decline between post-test and follow-up. The findings suggest that mindfulness-based group interventions are effective in enhancing attention regulation and emotional maturity in adolescents, with benefits sustained over time. This intervention may serve as a practical tool for psychological development and emotional support in school-based settings.